2011
DOI: 10.1007/s00784-011-0517-z
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical analysis of alveolar bone stress around implants with different thread designs and pitches in the mandibular molar area

Abstract: Threaded implants have been shown to play an important role in increasing mechanical osseointegration. The aim of this study was to determine bone stress distribution when using different types of implant thread pitches and designs. Five 3D finite element models were constructed to simulate bone stresses induced in implant bodies with two types of thread form: triangular ("Tri" prefix) and trapezoidal ("Trap" prefix). The former had thread pitches of 0.8, 1.2, and 1.6 mm, while the latter had thread pitches of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 27 publications
2
42
0
8
Order By: Relevance
“…To validate the numeric models, a comparison was made with the data in the literature. The levels of stress and deformation found in the present study conform with those found in other finite element analyses 19,21,22 . However, some assumptions were adopted in this study: the bone-implant interface was completely in contact, as in a perfect osseo-integration; the cortical and medullary bones were assumed to be linearly elastic -situations that, clinically, are not always true.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…To validate the numeric models, a comparison was made with the data in the literature. The levels of stress and deformation found in the present study conform with those found in other finite element analyses 19,21,22 . However, some assumptions were adopted in this study: the bone-implant interface was completely in contact, as in a perfect osseo-integration; the cortical and medullary bones were assumed to be linearly elastic -situations that, clinically, are not always true.…”
Section: Discussionsupporting
confidence: 81%
“…Several authors have suggested that an increase in the diameter favors the biomechanical issue for peri-implant osseous maintenance [14][15][16] . However, there are other studies that disagree with this 11,[17][18][19] .…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…In order to improve the osseointegration of titanium implants, several designs were generated throughout the past 20 years. 5,6 Besides modifications in implant surface structure, the implant design itself has been the target of variations in both its macro-and microproperties. The former was the primary variable of the present study, and two implant types displaying a different macro-design were considered.…”
Section: Introductionmentioning
confidence: 99%
“…The material properties of the INT model are listed in Table 1 and were chosen from previous studies [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. All seven ligaments were simulated by ten node link elements with resistance tension only, and they were arranged in the anatomical direction given by the text book [54]; the cross-sectional area of each ligament was obtained from previous studies [47,[52][53][54].…”
Section: Normal Discmentioning
confidence: 99%